Modernisasi Pendidikan Islam di Indonesia - Ruqoiyah, Ruqoiyah (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2019)
To build and foster a modern society, education is a very important part as a medium for transformation of values, culture and knowledge. Therefore, the thinking and institutions of Islamic education must be modernized. The establishment of IAIN played a very important role in influencing the modernization of Indonesian Islam. He became the mouthpiece of progressive Islamic thinkers who managed to move the wave of Islamic thought productively. Meanwhile, the dynamics and dialectics between conservative romanticism that always look into the past, and progressivists who always want to reconstruct Islam into the future, are a latent agenda of Muslims throughout history. Finally, the modernization movement must be continuously carried out while still paying attention to the basic principles of Islam that already exist and are agreed upon so that they will have a positive impact on the progress of Islamic education.